A Simple Spontaneous Vitreal Reflux Collecting Procedure During Intravitreal Injection: Set-Up and Validation Studies. (2nd July 2016) - Cacciamani, Andrea; Parravano, Mariacristina; Scarinci, Fabio; Esposito, Graziana; Varano, Monica; Micera, Alessandra
ABSTRACT: Aim : To set-up a simple technique for collecting spontaneous vitreal reflux (VR) in patients undergoing intravitreal injection. Both total protein concentration and vascular endothelial growth factor (VEGF)/Interleukin 13 (IL13) levels were used to validate the technique. Methods : Sixty consecutive patients with neovascular age-related macular degeneration (nAMD, vitreal reflux drop, VR) and 10 patients underwent vitrectomy for macular hole (whole vitreous removal) were enrolled for the study as controls. Thirty-three out of 60 patients were also subjected to tear sampling. VR sampling was performed after the intravitreal injection. Four sampling tools (10 Schirmer strips, 10 microsponges, 20 millipore filters; 20 micropipettes) were tested. Analysis of protein concentration/composition was performed between VR samples and vitreous samples to analyze the difference. The concentration of VEGF and IL 13 levels between cases and control samples were compared. Results : Millipore and micropipette techniques allowed the collection of higher protein concentrations in VR samples, comparison of both protein concentrations revealed no significant difference in the protein profile. However, the micropipette sampling was found easier to perform and did not require additional protein extraction from a solid support (membrane). Indeed, tear proteins and drug contaminants were not detected in micropipette samples. Increased VEGF levels were detected in naive VR group and to a less extend in VR group of nAMD patients undergoing intravitreal injection, with respect to the controls (macular holes). No significant differences in IL13 levels were quantified in nAMD sub-groups, as compared to naive and controls. Conclusions : Overall, we provide evidence for a safe method for sampling VR at the end of intravitreal injection. This procedure might represent an interesting approach either for the prognosis of disease or monitoring the efficacy of intravitreal therapy.